Cyberbullying Found in Commentary on English Educational Youtube Channel for High School Students - Salsabila Afifa; Yelfiza Yelfiza; Yola Merina (Edumaspul: Jurnal Pendidikan, 2022)
Cyberbullying is a phenomenon that occurs in social networks such as (e-mail, Facebook, Instagram, Twitter, blogs, YouTube, etc.) where internet access is very easy to get. Cyberbullying occurs on an intentional basis based on 7 types of cyberbullying according to Styron et al. (2016) namely: Flaming (burning), Online Harassment (distraction), Cyberstalking, Denigration (defamation), Impersonating (impersonation), Trickery (deception), Exclusion (exception in online groups). The background of this research is based on a real basic phenomenon that can be seen on various social media platforms, cyberbullying has a bad impact on the generation of students and the education of teenagers. Researchers conducted this research on a YouTube channel commentary platform with video content about learning English for high school students/equivalent. The method used in this research is the phenomenological method, where the data can be obtained based on real events. Of the seven types of cyberbullying, researchers found three types of cyberbullying in youtube comments based on the scope of data sources in the youtube channel comments found by researchers, types of data found were as follows: Flaming, Online Harassment, and Denigration.